Utilization of Leaf Chopping Machine as an Environmental School Support at SDN Mojolangu 2 Malang Municipality (TEKAD : Teknik Mengabdi, 2025)
Effective and environmentally sound learning is the main goal of the school because it is able to integrate theory with real practice in the surrounding environment. One example is the utilization of organic waste, such as dry leaves and twigs, to be processed into compost for the school garden. This approach not only supports practical science lessons, but also fosters environmental awareness early on in elementary school students. So far, science learning is often only theoretical in the classroom. To make it easier for students to understand and make learning fun, tools such as a leaf shredder are needed. This machine helps solve the problem of using manual tools such as small scissors that are less efficient. The shredder can turn organic waste into small pieces that are ready to be processed into compost, supporting creative and innovative activities in learning. The solution offered is training in the design and manufacture of leaf shredding machines as well as the introduction of a machine model that is easy to use and maintain. This machine is donated to the school to support the Adiwiyata School program, which is an environmentally friendly school. The chopping machine serves as a learning tool for students and school managers, encouraging creative, productive, and environmentally friendly characters. The results obtained include a model of the chopping machine along with a guide to its use. With this machine, the learning atmosphere becomes more interactive, increases student understanding, and supports the formation of environmentally friendly characters. The level of user satisfaction with this chopping machine is very high, making it a real contribution in creating an environmentally friendly and innovative school environment.